Minimally invasive technique of monoaxial percutaneous screws and instrumentational maneuvers in thoracolumbar and lumbar fractures. Issue 12 (December 2022) - Yin, Nuo; Du, Li; Pan, Mingmang; Xue, Feng; Shen, Yuchun; Ding, Liang
Abstract: Objectives: Percutaneous pedicle screw fixation (PPSF) has been a common surgery for treating thoracolumbar and lumbar fractures. Many studies have reported PPSF is associated with poor reduction. We present a reliable method by using short-segment monoaxial percutaneous screws and instrumentational maneuvers to reduce the spine. This study aimed to evaluate radiological and clinical results of this method of reduction compared to traditional polyaxial screws method in treating thoracolumbar and lumbar fractures. Methods: From February 2015 to February 2021, 64 patients with thoracolumbar and lumbar fractures in our department were retrospectively reviewed and divided into experimental group and control group according to different treatment methods. The experimental group was treated with short-segment monoaxial percutaneous screws (which were inserted at the adjacent vertebrae one level above, one level below the fracture, and the fractured vertebra) and instrumentational maneuvers method, while the control group was treated with traditional polyaxial screws method. The operation time was recorded. Visual analogue scale (VAS) and Oswestry disability index (ODI) were assessed as the clinical outcomes. The anterior height of the injured vertebra (AVH), the kyphosis cobb angle and the vertebral wedge angle were used to evaluate the fracture radiological reduction. Results: A total of 64 patients were enrolled including 31 in the experimental group and 33 in the control group. There were no significant difference in operation time, AVH, the kyphosis cobb angle, the wedge angle of injured vertebra, VAS and ODI score between the two groups in preoperation. In each group, there were significant differences in the AVH, the kyphosis cobb angle and wedge angle of injured vertebra between preoperation and immediate postoperation. In each group, there were significant differences in VAS and ODI score between the preoperation and last follow-up. The total correction rates of AVH, the kyphosis cobb angle and the wedge angle of injured vertebra were significantly higher in the experimental group than those in the control group, while the loss of correction was significantly lower than the control. Conclusions: The reduction technique using monoaxial percutaneous screws and instrumentational maneuvers for thoracolumbar and lumbar fractures exhibited better radiological results and satisfying functional outcomes when compared to traditional polyaxial screws.